Association of HLA‐DRB109:01 with severe COVID‐19 - Anzurez, Alitzel; Naka, Izumi; Miki, Shoji; Nakayama‐Hosoya, Kaori; Isshiki, Mariko; Watanabe, Yusuke; Nakamura‐Hoshi, Midori; Seki, Sayuri; Matsumura, Takayuki; Takano, Tomohiro; Onodera, Taishi; Adachi, Yu; et al. (HLA, 2021)
HLA‐A, ‐C, ‐B, and ‐DRB1 genotypes were analyzed in 178 Japanese COVID‐19 patients to investigate the association of HLA with severe COVID‐19. Analysis of 32 common HLA alleles at four loci revealed a significant association between HLA‐DRB1*09:01 and severe COVID‐19 (odds ratio [OR], 3.62; 95% CI, 1.57–8.35; p = 0.00251 [permutation p value = 0.0418]) when age, sex, and other common HLA alleles at the DRB1 locus were adjusted. The DRB1*09:01 allele was more significantly associated with risk for severe COVID‐19 compared to preexisting medical conditions such as hypertension, diabetes, and cardiovascular diseases. These results indicate a potential role for HLA in predisposition to severe COVID‐19.